2016
DOI: 10.1089/chi.2015.0253
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prepregnancy Body Mass Index and Gestational Weight Gain with Size, Tempo, and Velocity of Infant Growth: Analysis of the Newborn Epigenetic Study Cohort

Abstract: Background: The first 1000 days of life is a critical period of infant growth that has been linked to future adult health. Understanding prenatal factors that contribute to variation in growth during this period could inform successful prevention strategies.Methods: Prenatal and maternal characteristics, including prepregnancy obesity and gestational weight gain were evaluated in relation to weight growth trajectories during the first 24 months of life using the SuperImposition by Translation and Rotation (SIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
4
25
1
Order By: Relevance
“…developing offspring [11]. Both pre-pregnancy obesity and excessive gestational weight gain (GWG) independently contribute to cardiometabolic function, including obesity, in offspring [3][4][5]. With 25% of conceptions occurring among obese women in the U.S [12]., maternal obesity before and during pregnancy is perhaps one of the most common intrauterine risk factors for childhood obesity for which we have limited mechanistic insights.…”
mentioning
confidence: 99%
“…developing offspring [11]. Both pre-pregnancy obesity and excessive gestational weight gain (GWG) independently contribute to cardiometabolic function, including obesity, in offspring [3][4][5]. With 25% of conceptions occurring among obese women in the U.S [12]., maternal obesity before and during pregnancy is perhaps one of the most common intrauterine risk factors for childhood obesity for which we have limited mechanistic insights.…”
mentioning
confidence: 99%
“…When considering the maternal factors that may affect the growth parameters of the newborn, there was an increase of birth weight with mother’s prepregnancy weight in both genders. Studies conducted in São Paulo, 16 Southeast United States 17 and Tianjin, China, 18 showed similar results. However, a study conducted in Taiwan found that mothers whose body mass index (BMI) was 24–27 (normal) had significantly higher neonatal birth weight than those mothers with a BMI >27 and <18.5.…”
Section: Discussionmentioning
confidence: 52%
“…The effects of excessive weight gain in pregnancy have been extensively studied and linked to adverse maternal and neonatal outcomes [1, 25, 26]. As the implications of excessive GWG could be profound and with the rising prevalence of overweight and obesity in the Southeast Asian [27, 28], understanding the characteristics of GWG and making appropriate GWG advice for overweight and obese Singaporean women prior to and during pregnancy is important.…”
Section: Discussionmentioning
confidence: 99%